IMPLEMENTATION OF A DEEP LEARNING APPROACH IN DEVELOPING THE COGNITIVE ABILITIES OF 4-5 YEAR-OLD CHILDREN - Ni Luh Rista Dewi; Relin D.E; I Made Dian Saputra (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2026)
This study aims to analyze the implementation of the immersive learning approach in developing the cognitive abilities of 4-5-year-old children in early childhood education institutions. The background of this research is based on the importance of appropriate stimulation during the golden age period, as well as the continued dominance of teacher-centered learning practices, which do not support optimal cognitive development. This study used a qualitative approach with data collection techniques through observation, interviews, and documentation. The results indicate that the implementation of the immersive learning approach was carried out through active, contextual, and experience-based learning activities, such as educational games, exploration, and simple project-based activities. The teacher acted as a facilitator, providing stimulation through open-ended questions to encourage children's thinking processes. Furthermore, observations showed an increase in children's cognitive abilities, characterized by the ability to observe, classify, compare, and solve simple problems. Thus, the immersive learning approach has proven effective in improving the cognitive abilities of 4-5-year-old children through a meaningful, active learning process that is appropriate to the developmental characteristics of early childhood.